Optimizing educational personnel for effective teaching factory implementation in vocational schools: A case study - Widiatna, Alexius Dwi; Permana, Natalis Sukma (UIN Raden Mas Said Surakarta, 2025)
There is a growing need to enhance the alignment between vocational education and industry requirements, yet research on the role of educational personnel management in optimizing teaching factory implementation remains limited. This study explores the management of educational personnel in the implementation of teaching factories as an innovative learning model. A teaching factory represents a dynamic and practical learning environment designed to integrate educational processes with industrial practices, bridging the gap between the competencies of students in vocational schools and the demands of industry for skilled workers. The research employs a qualitative approach using a case study method. Data were gathered through observation, participatory observation, documentation, and in-depth interviews with key stakeholders, including the principal, the head of personnel, and the heads of expertise programs. Data analysis involved processes of data condensation, data display, and conclusion drawing. The findings demonstrate that St. Mikael’s approach to educational personnel management is both innovative and effective. By investing in teacher development, fostering collaboration, and addressing challenges proactively, the school has created an environment where both teachers and students thrive. These strategies not only enhance the competencies of educators but also prepare students to meet the demands of the modern workforce. The insights from this study provide valuable lessons for other vocational schools aiming to implement teaching factory models and align education with industry needs.